Analysis of Consumer Characteristics of QRIS Users at the Purchase Decision Stages for Hydroponic Vegetables at Pontianak Hydroponic Center - Hadisza Anggreni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The increasing public awareness of healthy lifestyles and the development of digital payment systems have encouraged the consumption of hydroponic vegetables as well as the use of the Quick Response Code Indonesian Standard (QRIS) as a transaction method. Consumer characteristics are important information for understanding purchasing behavior at each stage of the purchasing decision process. This study aims to analyze the characteristics of consumers using QRIS based on the stages of the purchasing decision process for hydroponic vegetables at Pontianak Hydroponic Center (PHC). The research was conducted in November 2025 using a survey method involving 100 respondents selected through purposive sampling. Data analysis was carried out descriptively using bivariate analysis through cross-tabulation between consumer characteristics and stages of the purchasing decision process. The results show that QRIS-using consumers are predominantly residents of South Pontianak (41%), aged 26–35 years (47%), female (63%), high school graduates (34%), married (66%), working as housewives (43%), and earning IDR 3,500,000–5,000,000 per month (36%). Across the stages of the purchasing decision process, these characteristics indicate that the main consumers of hydroponic vegetables using QRIS are individuals in productive age groups with high health awareness and familiarity with digital transactions.